Transformation of MSME Management in Barru Regency in the Digital Era: A Qualitative Analysis Using NVivo - Hasi, Lukman; Ariyadi, A. (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the transformation of Micro, Small, and Medium Enterprises (MSME) management in Barru Regency in the digital era. The research focuses on business planning, financial management, marketing strategies, and the utilization of digital technology by MSME actors. This study employs a qualitative approach, with data collected through in-depth interviews, observation, and documentation. Informants were selected using purposive sampling techniques. Data analysis was conducted using NVivo software to systematically identify themes, patterns, and relationships among categories. The results indicate that the transformation of MSME management in Barru Regency still faces several challenges, particularly in digital literacy, access to technology, and human resource limitations. However, some MSME actors have begun to adopt digital platforms such as social media and marketplaces to expand market reach and improve operational efficiency. Government support through training and mentoring programs has also contributed to enhancing managerial capacity. This study recommends strengthening digital-based policies, improving technological literacy, and fostering cross sector collaboration to ensure the sustainability of MSMEs in the digital era.